Suicide : Foucault, history and truth - Marsh, Ian, 1952- (Cambridge : Cambridge University Press, 2010)
'In an original and provocative study of suicide, Ian Marsh examines the historical and cultural forces that have influenced contemporary thought, practices and policy in relation to this serious public health problem. Drawing on the work of French philosopher Michel Foucault, the book tells the story of how suicide has come to be seen as first and foremost a matter of psychiatric concern. Marsh sets out to challenge the assumptions and certainties embedded in our beliefs, attitudes and practices concerning suicide and the suicidal, and the resulting account unsettles and informs in equal measure. The book will be of particular interest to researchers, professionals and students in psychology, history, sociology and the health sciences'--Provided by publisher.
'This book, which is for the most part influenced by the work of Michel Foucault, critically examines contemporary approaches to the problem of suicide. From Foucault comes a focus on relations of power, knowledge and the subject, and it is argued that it is possible to identify certain principles and strategies of analysis from Foucault's own studies (e.g. Madness and Civilization, 1965RFA-123; Discipline and Punish, 1977RFA-126 and The History of Sexuality, Volume 1: An Introduction, 1981RFA-128) that can usefully be employed to interrogate the assumptions and certainties embedded in our beliefs, attitudes and practices concerning suicide and the suicidal'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Foucault, Michel, -- 1926-1984.; Suicide; Suicide -- History